(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
Master’s dissertation The socio-economic significance of the organization of employment through the mahalla system, the systemic solution of women’s problems, the peculiarities of their social support and the peculiarities of the new mechanism for joint solution of important issues of improving the living standards of the population. system organization status and its analysis. Analysis of the situation with the employment of unemployed women in Yunusabad district through the mahalla system and the situation with the employment of unemployed women in the district through the mahalla system. directions are given.